(untitled) (Stamford Journal of Microbiology, 2016)
Present study attempted to isolate and quantify the microorganisms from the pear samples collected within Dhaka metropolis. Out of the five samples studied, total viable bacterial count and the total coliform count were near about 105 cfu/g and 104 cfu/g, respectively. Among the specific pathogens, prevalence of Salmonella spp. and Vibrio spp. were found only in two samples. Whereas Klebsiella spp, Pseudomonas spp. and Staphylococcus aureus were detected in all the samples studied. Fungal growth was also observed in each sample within the range of 8.8×104 9.5×104 cfu/g. The study of antibiogram revealed that, most of the pathogens were resistant to more than one antibiotic. Interestingly the pear samples showed no anti-bacterial activity against any of the laboratory isolates such as, Escherichia coli, Pseudomonas spp., Salmonella spp. and Bacillus spp. Stamford Journal of Microbiology, Vol.5(1) 2015: 1-4